Defending Earth's terrestrial microbiome - Averill, Colin; Anthony, Mark A; Baldrian, Petr; Finkbeiner, Felix; van den Hoogen, Johan; Kiers, Toby; Kohout, Petr; Hirt, Eliane; Smith, Gabriel Reuben; Crowther, Tom W (Nature microbiology, 2022)
Microbial life represents the majority of Earth's biodiversity. Across disparate disciplines from medicine to forestry, scientists continue to discover how the microbiome drives essential, macro-scale processes in plants, animals and entire ecosystems. Yet, there is an emerging realization that Earth's microbial biodiversity is under threat. Here we advocate for the conservation and restoration of soil microbial life, as well as active incorporation of microbial biodiversity into managed food and forest landscapes, with an emphasis on soil fungi. We analyse 80 experiments to show that native soil microbiome restoration can accelerate plant biomass production by 64% on average, across ecosystems. Enormous potential also exists within managed landscapes, as agriculture and forestry are the dominant uses of land on Earth. Along with improving and stabilizing yields, enhancing microbial biodiversity in managed landscapes is a critical and underappreciated opportunity to build reservoirs, rather than deserts, of microbial life across our planet. As markets emerge to engineer the ecosystem microbiome, we can avert the mistakes of aboveground ecosystem management and avoid microbial monocultures of single high-performing microbial strains, which can exacerbate ecosystem vulnerability to pathogens and extreme events. Harnessing the planet's breadth of microbial life has the potential to transform ecosystem management, but it requires that we understand how to monitor and conserve the Earth's microbiome.
Keywords: mikrobiota; Biodiversity; Earth, Planet; Soil; biodiverzita; lesy; Animals; půda; Microbiota; Země (planeta); zvířata; Forests